Effects of mannanoligosaccharide and sodium chlorate on growth performance of nursery pigs during an acute enteric disease challenge with salmonella enterica serotype typhimurium - Burkey, T.E.; Nietfeld, Jerome C.; Johnson, B.J.; Minton, J. Ernest; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 28-day experiment was conducted to compare the effects of feeding mannanoligosaccharides (mannan) and sodium chlorate (chlorate) to weanling pigs as a possible substitute for the commonly used antimicrobialcarbadox. Pigs were fed experimental diets for 2 wk, then challenged orally with Salmonella enterica serotype typhimurium to establish enteric disease. Average daily gain and ADFI were greater for pigs fed carbadox than all other treatments in the 2 wk following infection. During the first week after infection, pigs fed chlorate had greater G/F than control pigs, and pigs fed mannan tended to have greater G/F than control pigs. There were no differences in feed efficiency among treatments during the second week following infection.
Keywords: Mannanoligosaccharides; Sodium Chlorate; Antimicrobials; Weanling pigs; Swine